Causal role of ischemic heart disease in ovarian cancer subtypes - Jianhai Chen; Huabin He; Ling Gao (Discover Oncology)
Abstract Background Ischemic heart disease (IHD) may share biological mechanisms with cancer, including ovarian cancer, through pathways such as chronic inflammation and oxidative stress. However, the relationship between IHD and ovarian cancer subtypes remains unclear. This study used Mendelian randomization (MR) to explore potential causal associations. Methods A two-sample MR analysis was conducted using genetic instruments for IHD from large-scale genome-wide association studies (GWAS). The inverse-variance weighted (IVW) method was used as the primary analysis, supported by MR-Egger, weighted median, and MR-PRESSO for sensitivity analyses. Results No significant association was found between IHD and overall ovarian cancer risk (OR = 0.97, 95% CI 0.92–1.03, P = 0.378). However, IHD was linked to a reduced risk of endometrioid ovarian cancer (OR = 0.86, 95% CI 0.76–0.98, P = 0.027). No associations were observed for serous, mucinous, or clear cell ovarian cancers. Sensitivity analyses confirmed robust findings. Conclusions IHD may confer a protective effect against endometrioid ovarian cancer but does not influence overall ovarian cancer risk. These findings highlight the need for further research into subtype-specific mechanisms.